LABOUR WELFARE PRACTICES AND SOCIAL SECURITY IN INDUSTRIES - K.B.RAVINDRA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
Labour welfare and social security has got a lot of significance with Public Sector,Private Sector and also Multinational Companies.Labour welfare activities in an industrialised society has far reaching impact not only on the work force but also on all facets of human resources.Labour welfare includes all such activities which not only secure existential necessities but also ensures improvement in the spiritual,emotional and other aspects of a worker.The aspect of labour welfare requires an honest and serious approach that money and environment given to employees never go waste. A happy employee is a productive employee.A study on labour welfare and social security is an effort to be perfected in the art of managing people and in these days the most important management is peoples management.Welfare schemes should be regarded as a wise investment which should and usually does bring a profitable return in the form of greater efficiency.In the above background, the article provides a detailed insight in to the various aspects of labour welfare and social security in Indian Industries.